THE PRINCIPAL’S LEADERSHIP IN MOVER SCHOOL: QUALITATIVE STUDY AT ELEMENTARY SCHOOLS - Hema Malini; Nurtanio Agus Purwanto; Fabiola Lagarens; Asrin Asrin (Jurnal Eduscience)
Purpose: This study aims to determine the leadership of school principals, including (1) leadership roles, (2) innovations, and (3) supporting and inhibiting factors of school principals' leadership in elementary-mover schools in Yogyakarta city.